2012
DOI: 10.1371/journal.ppat.1002567
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of the Apicomplexan Parasites Toxoplasma gondii and Neospora caninum: Coccidia Differing in Host Range and Transmission Strategy

Abstract: Toxoplasma gondii is a zoonotic protozoan parasite which infects nearly one third of the human population and is found in an extraordinary range of vertebrate hosts. Its epidemiology depends heavily on horizontal transmission, especially between rodents and its definitive host, the cat. Neospora caninum is a recently discovered close relative of Toxoplasma , whose definitive host is the dog. Both species are tissue-dwelling Coccidia and members of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
230
2
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(265 citation statements)
references
References 85 publications
15
230
2
18
Order By: Relevance
“…Transcriptional comparisons between T. gondii and Neospora caninum, a fellow coccidian that is more diverged from T. gondii than H. hammondi, have been reported (65). N. caninum tachyzoites have significantly lower ROP16 transcript levels than T. gondii, and it was proposed that despite the conserved leucine residue crucial for ROP16-driven STAT3 phosphorylation in N. caninum ROP16, this strain of N. caninum would be unlikely to modulate the STAT3 (or possibly STAT6) pathway (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional comparisons between T. gondii and Neospora caninum, a fellow coccidian that is more diverged from T. gondii than H. hammondi, have been reported (65). N. caninum tachyzoites have significantly lower ROP16 transcript levels than T. gondii, and it was proposed that despite the conserved leucine residue crucial for ROP16-driven STAT3 phosphorylation in N. caninum ROP16, this strain of N. caninum would be unlikely to modulate the STAT3 (or possibly STAT6) pathway (65).…”
Section: Discussionmentioning
confidence: 99%
“…N. caninum tachyzoites have significantly lower ROP16 transcript levels than T. gondii, and it was proposed that despite the conserved leucine residue crucial for ROP16-driven STAT3 phosphorylation in N. caninum ROP16, this strain of N. caninum would be unlikely to modulate the STAT3 (or possibly STAT6) pathway (65). This has yet to be tested empirically, and attempts to align the upstream regions of NcROP16, HhROP16, and TgROP16 were not possible given the high divergence of the NcROP16 upstream sequence.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no rhoptry protein has been described and characterized in N. caninum and only comparative genomics of T. gondii and N. caninum revealed that although both the genome and gene expression are remarkably conserved between species, some rhoptry genes are highly divergent (Reid et al 2012). However, several studies from our group demonstrated that a recombinant, bacterially expressed C-terminal moiety of NcROP2Fam-1 (formerly designated recNcROP2) induced highly effective immunity against challenge infection with N. caninum tachyzoites in both cerebral and fetal infection mouse models (Debache et al 2008(Debache et al , 2009(Debache et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Toxoplasma gondii and Neospora caninum are very closely related tissue-dwelling Coccidia that share many biological features (1). The two parasites diverged ϳ28 million years ago, but their genome size and gene content and expression have been remarkably conserved; among the genes shared by T. gondii and N. caninum, 40% have no orthologues in any other Apicomplexa (e.g., Plasmodium and Cryptosporidium) (2). T. gondii affects up to one-third of the human population and is responsible for severe infections associated with the central nervous system (3).…”
mentioning
confidence: 99%